PERFORMANCE STUDIES: PERGESERAN WADIAN DADAS DARI RITUAL KE RUANG PERTUNJUKAN - Habibi, Budi Jaya (Jurnal Seni dan Pembelajaran, 2024)
Wadian Dadas in the realm of performance studies theory pioneered by Richard Schechner relates and combines Maruska Svasek's concept of transit-transitions-transformations. From the perspective of performance studies, Wadian Dadas experiences shifts in meaning, values, identity formation, and emotional subjectivity. The shift begins with the studio as a new form of art ownership (not replacing the role of Wadian Dadas, but only inspired by the concept idea of Wadian Dadas) which then transforms into the Dance of Gelang Dadas. The Dance of Gelang Dadas is modified and developed, and then practiced in performances for entertainment or tourism. Therefore, various aspects emerge to preserve the art so that Wadian Dadas from the ritual can be practiced in performance spaces that can be enjoyed and watched by the public without a long period of time.